(untitled) (Third Sector Social Economic Review, 2023)
Changes in the economic and technological area have had significant effects in the banking sector as well as in many other sectors. The service production process and workflow forms in the sector have been transformed in the context of new technologies, and this transformation has led to significant results on the qualification levels of the employees. In this study, it is aimed to reveal how the transformation in the labour process has caused a differentiation in the qualification levels of the banking sector employees, based on Braverman’s disqualification thesis. Within the scope of the research, a qualitative research design based on in-depth interview management was preferred. In this respect, interviews were conducted with 32 people, including managers, directors, officials, assistants and service personnel, who were considered sufficient to represent the conceptual generalization of the relationship between the change in the labour processes of bank employees and their qualifications. The increasing use of technology in banking sector has led to a gradual loss of qualifications in the areas of physical/mental effort, experience, responsibility and decision-making of employees and has caused the employees to get away from the information included within the mentioned technologies. Similarly, technological change has created the problem of routinization of work flow processes.